Housing busts and household mobility: An update - Fernando Ferreira; Joseph Gyourko; Joseph Tracy (Federal Reserve Bank of New York, 2011)
This paper provides updated estimates of the impact of three financial frictions - negative equity, mortgage lock-in, and property tax lock-in - on household mobility. We add the 2009 wave of the American Housing Survey (AHS) to our sample and also create an improved measure of permanent moves in response to Schulhofer-Wohl's (2011) critique of our earlier work (2010). Our updated estimates corroborate our previous results: Negative equity reduces household mobility by 30 percent, and 1,000 of additional mortgage or property tax costs reduces household mobility by 10 to 16 percent. Schulhofer-Wohl's finding of a slight positive correlation between mobility and negative equity appears due to a large fraction of false positives, as his coding methodology has the propensity to misclassify almost half of the additional moves it identifies relative to our measure of permanent moves. This also makes his mobility measure dynamically inconsistent, as many transitions originally classified as a move are reclassified as a nonmove when additional AHS panels become available. We conclude with directions for future research, including potential improvements to measures of household mobility.
Keywords: R21; R31; R38; 330; negative equity; mobility